The Dimensions of Distance Learning and its impact on achieving Customer Value (Zien Journal of Social Sciences and Humanities, 2022)
Today's distance learning system seeks a realistic and tangible endeavor that allows the learner to advance to the highest levels of education, such as obtaining a doctorate. It depends on different means of receiving science, so that the learner can attend classes or different conferences and benefit from them wherever he is.This research aims to identify the dimensions of distance learning and its impact on achieving customer value in the public universities of the Middle Euphrates Technical Region. This research derives its importance by paying attention to the opinions of professors and students and their impressions about the dimensions of distance learning and their impact on the value of the customer.The problem of the research lies in determining to what extent distance learning dimensions can be considered as having an impact on achieving the value of the customer (the learner) in the universities surveyed? The descriptive analytical method was used for its suitability and research purposes. The research sample was chosen randomly from (150) professors and graduate students in the researched universities, and the research reached a number of results that helped to come up with many conclusions that confirmed the overall validity of the research trends and their premises, and in the light of those conclusions, a set of recommendations were made In a manner that stressed the need for the universities surveyed to pay attention to the dimensions of distance learning to achieve customer value.